2013
DOI: 10.1210/en.2012-2074
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Effects on Prostate Cancer Cell Migration and Invasion Are Mediated by PGE2 through Activation of PI3K/AKT/mTOR Pathway

Abstract: TGF-β plays an important role in the progression of prostate cancer. It exhibits both tumor suppressor and tumor-promoting activities. Correlations between cyclooxygenase (COX)-2 overexpression and enhanced production of prostaglandin (PG)E2 have been implicated in cancer progression; however, there are no studies indicating that TGF-β effects in prostate cancer cells involve PGE2 synthesis. In this study, we investigated TGF-β regulation of COX-1 and COX-2 expression in prostate cancer cells and whether the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
137
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(152 citation statements)
references
References 37 publications
11
137
0
4
Order By: Relevance
“…Here, our results suggested that the AKT/mTOR signaling pathway was involved in the autophagy activation by PGE1 treatment under HG. It was reported that PGE2 induced the activation of the PI3K/AKT/ mTOR pathway in prostate cancer cells or mast cell chemotaxis [17]. Based on our results, it was suggested that AKT/mTOR signal pathway was responsible for the regulation of PGE1 on autophagy.…”
Section: Discussionsupporting
confidence: 63%
“…Here, our results suggested that the AKT/mTOR signaling pathway was involved in the autophagy activation by PGE1 treatment under HG. It was reported that PGE2 induced the activation of the PI3K/AKT/ mTOR pathway in prostate cancer cells or mast cell chemotaxis [17]. Based on our results, it was suggested that AKT/mTOR signal pathway was responsible for the regulation of PGE1 on autophagy.…”
Section: Discussionsupporting
confidence: 63%
“…The abnormal activation of this pathway has been corroborated by epidemiological and experimental studies as a critical step toward the initiation and maintenance of human tumors. Previous research has demonstrated that PI3K/Akt triggers a cascade of multiple signals that regulate cancer cell proliferation, invasion, metastasis, survival as well as affecting prognosis (24,25). Thus, in this study, to explore the mechanisms involved in the miR-214-mediated increase in cell viability and resistance to apoptosis, we examined the involvement of PI3K/Akt signaling in these processes.…”
Section: Discussionmentioning
confidence: 97%
“…Based on these findings, the PI 3 K/Akt/mTOR pathway is believed to be a promising therapeutic target for the treatment of cancer, and small molecules that inhibit one or more of these kinases are now being introduced into the clinic and may have some activity [43,44]. For example, TGF-β increased COX-2 levels and PGE 2 secretion in prostate cancer cells which, in turn, mediate TGF-β effects on cell migration and invasion through the activation of PI 3 K/AKT/mTOR pathway [45]. Thioridazine, a well-known anti-psychotic agent was found to induce apoptosis by targeting the PI 3 K/Akt/mTOR pathway in cervical and endometrial cancer cells [46].…”
Section: Discussionmentioning
confidence: 99%